Implementation of a Pediatric Critical Care Focused Bedside Ultrasound Training Program in a Large Academic PICU*. Issue 3 (March 2015) - Conlon, Thomas W.; Himebauch, Adam S.; Fitzgerald, Julie C.; Chen, Aaron E.; Dean, Anthony J.; Panebianco, Nova; Darge, Kassa; Cohen, Meryl S.; Greeley, William J.; Berg, Robert A.; Nishisaki, Akira
Abstract : Objectives: To determine the feasibility and describe the process of implementing a pediatric critical care bedside ultrasound program in a large academic PICU and to evaluate the impact of bedside ultrasound on clinical management. Design: Retrospective case series, description of program implementation. Setting: Single-center quaternary noncardiac PICU in a children's hospital. Patients: Consecutive patients from January 22, 2012, to July 22, 2012, with bedside ultrasounds performed and interpreted by pediatric critical care practitioners. Interventions: A pediatric critical care bedside ultrasound program consisting of a 2-day immersive course followed by clinical performance with internal quality assurance review was implemented. Studies performed in the PICU following training were documented and reviewed against reference standards including subspecialist-performed ultrasound or clinical response. Measurements and Main Results: Seventeen critical care faculties and eight fellows recorded 201 bedside ultrasound studies over 6 months in defined core applications: 57 procedural (28%), 76 hemodynamic (38%), 35 thoracic (17%), and 33 abdominal (16%). A quality assurance review identified 23 studies (16% of all nonprocedural studies) as critical (affected clinical management or gave valuable information). Forty-eight percent of those studies (11/23) were within the hemodynamic core. The proportion of critical studies were not significantly different across the applications (hemodynamic, 11/76 [15%] vs thoracic and abdominal, 12/68 [18%]; p = 0.65). Examples of critical studies include evidence of tamponade secondary to pleural effusions, identification of pulmonary hypertension, hemodynamic assessment before tracheal intubation, recognition of hypovolemia and systemic vascular resistance abnormalities, determination of pneumothorax, location of chest tube and urinary catheter, and differentiation of pleural fluid from pulmonary consolidation. Conclusions: Implementation of a critical care bedside ultrasound program for critical care providers in a large academic PICU is feasible. Bedside ultrasound evaluation and interpretation by intensivists affected the management of critically ill children. Abstract : Supplemental Digital Content is available in the text.